Critical Care Nurses' Perceptions of Abuse and Its Impact on Healthy Work Environments in Five European Countries: A Cross-Sectional Study - Friganovic, Adriano; Slijepčević, Jelena; Režić, Slađana; Cristina Alfonso-Arias, Cristina; Borzuchowska, Monika; Constantinescu-Dobra, Anca; Coțiu, Madalina-Alexandra; Estel Curado-Santos, Estel; Dobrowolska, Beata; AGutysz-Wojnicka, Aleksandra; Hadjibalassi, Maria; Laurado-Serra, Mireia; et al. (My University, 2024)
Workplace violence is a prevalent phenomenon in hospital settings which critical care nurses are particularly exposed to. The aim of this study was to research abuse against Critical Care Nurses in five European countries, and its association with and impact on Healthy Work Environments.
Keywords: workplace violence; abuse; critical care; healthy work environment; nursing